Analisis Kinerja Keuangan pada Industri Tempe di Nagori Rambung Merah Kabupaten Simalungun - Sumaizar Sumaizar; Muhammad Rido; Eko Deswin Miechaels Siringo-Ringo (Politeknik Ganesha Medan, 2019)
This study aims to determine the financial performance of the tempe industri in Nagori Rambung Merah. To measure financial performance, an analysis tool called financial ratio analysis can be used. In carrying out this analysis, it is necessary to calculate financial ratios that include certain aspects. Financial statement analysis will give the best results when used in a combination to show changes in financial condition or operating performance over a given period. The data analysis method used is descriptive analysis and the data is presented in the form of balance sheet financial statements and income statements. This data processing uses the Microsoft Excel software package followed by financial ratio analysis by looking at the comparison of financial ratios, namely the ratio of liquidity, solvability, and profitability. In this way, it will be obtained the results of the analysis of the correct financial performance for the tempe industri in Nagori Rambung Merah.